The use of african language as media of teaching and learning in public schools in Mopani district (Limpopo Province):A critical analysis - Sithole, Kateko Lucy (University of Limpopo, 2019)
This thesis investigated the use of African languages as media of teaching and learning in public schools in Mopani District of Limpopo Province. The study was guided by a qualitative approach. A total of 30 educators from five primary schools participated in the study. Purposive sampling was used to select the participants. Interviews were used as a tool for data collection. Data from the interviews was analysed by means of thematic method of data analysis, and was presented in the form of themes. The results revealed that African languages are admired by most educators. The findings of this study revealed that it is possible to introduce African languages as media of teaching and learning in South Africa, but it will require an extensive preparation, which involves effective training of teachers and the acquisition of teaching and learning materials in African languages. The study also revealed that the current use of English and Afrikaans as media of teaching and learning contributes to poor academic performance of learners. The findings of the study have important implications for both learners and educators. The study will provide the National Department of Education with information it might need to review its language policy with regard to instructional languages. The study will also contribute towards knowledge of African languages as media of instruction, and will help school administrators and policy makers to understand challenges associated with the current medium of instruction and learner performance in schools in South Africa. All education stakeholders might be able to identify the causal factors of language failure rate in grade 12
Thesis (Ph.D.(African languages)) --University of Limpopo, 2019
Keywords: African languages; Mother tongue; Curriculum; Instruction; Media of teaching and learning; Educators; Learning; Academic perormance; Learners; 371.1022; Teaching; African languages; African language-Teaching and study